Mental Health and Quality of Life in Breast Cancer Patients: A Systematic Review - Sofyan Hadi Hasibuan; Akhmad Huda; Rosliana Dewi; Johan Budhiana; Iwan Permana; Maria Yulianti (Indonesian Journal of Global Health Research, 2025)
While survival rates of breast cancer patients have improved thanks to advances in early detection and treatment, patients often experience anxiety, depression and stress, which can worsen their emotional and physical recovery. Objective: this study aimed to identify and analyze the relationship between mental health and quality of life of breast cancer patients through a systematic review of the literature. Methods: This study was a systematic literature review using the PRISMA approach including qualitative, longitudinal, prospective, and cross-sectional studies published between 2020-2025 in English, without interventions or comparisons, focusing on articles reporting these relationships. Results: Based on a comprehensive literature search, a total of 36,229 articles were initially identified using keywords from four major academic databases: Scopus (2,578), PubMed (683), Sage Journals (31,999), and Web of Science (969). After removing duplicates and screening based on inclusion and exclusion criteria, 11 articles were selected for full-text review and final inclusion in the systematic review. Conclusions: These studies collectively revealed a consistent and significant relationship between mental health and quality of life (QoL) of breast cancer patients. Anxiety, depression, psychological inflexibility, and emotional distress were found to negatively impact QoL. This synthesis highlights the need for a comprehensive multidisciplinary approach in breast cancer care to support long-term survival.